2006
DOI: 10.1037/0022-006x.74.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a family-centered approach to the prevention of early conduct problems: 2-year effects of the family check-up in early childhood.

Abstract: Despite recent research indicating that 1 of the pivotal times for identifying pathways to early conduct problems is the toddler period, few family-based preventive interventions have been specifically designed to modify child disruptive behavior during this age period. This randomized trial tested the effectiveness of the Family Check-Up in sustaining maternal involvement and preventing the exacerbation of child conduct problems among 120 at-risk toddler-age boys, half of whom were randomly assigned to a trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
298
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(314 citation statements)
references
References 29 publications
12
298
0
4
Order By: Relevance
“…Self-efficacy and parental stress did not mediate this association . Others have found that parental stress and higher levels of difficulty in the child and the parent are predictors of greater engagement (Beauchaine, WebsterStratton & Reid, 2005;Shaw, Dishion, Supplee, Gardner & Arnds, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy and parental stress did not mediate this association . Others have found that parental stress and higher levels of difficulty in the child and the parent are predictors of greater engagement (Beauchaine, WebsterStratton & Reid, 2005;Shaw, Dishion, Supplee, Gardner & Arnds, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, with increasing frequency selective sector services are provided by community-based or 'grassroots' service providers: social service agencies, domestic violence shelters, foster and adoption agencies, and community or faith centers in high-risk communities (Ryan, 1999). Very little attention has been paid to the mental health status or access to care of children served by these community-based sectors (e.g., Gewirtz, Hart-Shegos, & Medhanie, in press;Shaw, Dishion, Supplee, Gardner, & Arnds, 2006), in contrast to the extant systems-of-care literature on mental health status and access in formal or governmental sectors. Just as selective prevention may be an underutilized and under-researched prevention mode, selective or secondary service sectors seem to be under-utilized prevention portals.…”
Section: Selective Prevention and Service Portalsmentioning
confidence: 99%
“…at a mental health clinic). Thus, while their infrastructure, staff expertise, and fluidity may present significant challenges, these agencies could potentially be critical portals for families, with the potential to truly engage families in providing and brokering children's prevention and mental health services (e.g., Shaw et al, 2006).…”
Section: Community Sectors-of-carementioning
confidence: 99%
“…The tiered model in Figure 1.1 shows the reach of these three types or intensities of intervention. Examples of the application of this type of tiered model include the Adolescent Transitions Program (Dishion and Kavanagh, 2002) and Family Check-Up (Shaw et al, 2006). Applying this model to CEV, we see that universal prevention would apply to communities as a whole, selective prevention would focus on the interventions that target CEV without determining whether the children have been adversely affected, and targeted prevention programs would be reserved for the minority of children who experienced violence and are also displaying some lasting adverse effects.…”
Section: State Of the Evidence For Improving Outcomes For Children Exmentioning
confidence: 99%
“…Models of such programs come from the Adolescent Transitions Program (Dishion and Kavanagh, 2002) and Family Check-Up (Shaw et al, 2006), both designed to address behavior problems and delinquency. In regard to violence exposure, the concept of trauma-informed care within communities and settings at various levels of care is gaining momentum (Hanson and Lang, 2016).…”
Section: Future Directionsmentioning
confidence: 99%